Pengaruh Stres Kerja, Lingkungan Kerja,Kepercayaan Diri terhadap Kinerja Karyawan PT. XYZ - Sari, Pinka Julinda; Tjahyanti, Setia (Media Bisnis, 2023)
This research was intended to analyse determine the effect of work stress, work environment, and self-confidence on the employee performance at PT. XYZ. The population in this study were employees at PT. XYZ has as many as 505 employees and the sample used was 96 employee. The sampling technique used is non-probability sampling with a purposive sampling technique in which the sampling technique is taken with certain considerations. The data collection technique by distributing questionnaires using a likert scale. The data was then analyzed using statistical data. The method used in this research is a descriptive and causal method with testing using multiple linear regression analysis. Based on the research results, the data in this study show that work stress, work environment, and self-confidence positive affect employee performance at PT. XYZ